Learning and Leading: Resistance, Subaltern Leadership and the Making of Two Bhil Community Leaders from the Narmada Valley, Western India - Vikramaditya Thakur (South Asia Multidisciplinary Academic Journal, 2019)
This paper studies subaltern agency and the changing nature of leadership in rural western India among the Bhil Scheduled Tribe or Adivasi group in the wake of the anti-dam movement initiated by urban middle-class activists of the Narmada Bachao Andolan (NBA; also Save Narmada Campaign). Drawing on fieldwork data along with oral history, archival research, government records, vernacular records and dailies, it analyzes the politics of displacement and resettlement due to the Sardar Sarovar Dam on the River Narmada as a lived experience of two ordinary Bhil men from the submergence villages in Maharashtra state across three decades from 1985–2016. The NBA-led movement acts as a form of political education for the two Bhils who assume leadership, displacing both traditional Bhil leaders and external activists to guide their community deftly to the resettlement colonies by making claims on the Indian state, and helping to recreate life and livelihood for themselves and their fellow Bhils in the new setting.